Bioactive Lignan Honokiol Alleviates Ovarian Oxidative Stress in Aging Laying Chickens by Regulating SIRT3/AMPK Pathway - Yiqiu Chen; Zhaoyu Yang; Jingchun Bai; Xinyu Wang; Qiongyu Yuan; Yuling Mi; Caiqiao Zhang (MDPI AG, 2024)
Aging is not only a key internal cause of age-related diseases in humans but also poses a threat to the productivity of farm animals with longer breeding cycles, such as laying chickens. Various measures were taken to prolong the laying period by reducing oxidative stress to improve poultry ovarian functions. Within the mitochondria, SIRT3, a member of the Sirtuin family, plays an important role in post-translational modifications and the regulation of protein activities involved in energy metabolism and oxidative response. This study aimed to investigate the alleviating effect of a bioactive lignan Honokiol (HKL) on oxidative stress in aging chicken ovaries in order to retard decline in egg production. The results showed that HKL treatment restored the abnormal balance between cell proliferation and apoptosis, and it enhanced the antioxidant capacity of the H2O2-induced small white follicles (SWFs) by activating the SIRT3/AMPK pathway. Moreover, HKL significantly increased total egg production, the number of yellow follicles, and the mRNA expression of yolk synthesis and deposition-related genes, serum estrogen, and antioxidant levels. These findings suggest that HKL holds promise in enhancing the egg productivity of aging laying chickens by promoting yolk deposition and reducing ovarian oxidative stress.